2000
DOI: 10.1007/s000180050502
|View full text |Cite
|
Sign up to set email alerts
|

Radical catalysis of B 12 enzymes: structure, mechanism, inactivation, and reactivation of diol and glycerol dehydratases

Abstract: Enzymatic radical catalysis is defined as a mechanism of catalysis by which enzymes catalyze chemically difficult reactions by utilizing the high reactivity of free radicals. Adenosylcobalamin (coenzyme B12) serves as a cofactor for enzymatic radical reactions. The recent structural analysis of adenosylcobalamin-dependent diol dehydratase revealed that the substrate 1,2-propanediol and an essential potassium ion are located inside a (beta/alpha)8 barrel. Two hydroxyl groups of the substrate coordinate directly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
149
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(155 citation statements)
references
References 93 publications
3
149
0
3
Order By: Relevance
“…All of the glycerol and diol dehydratases characterized so far belong to class II of coenzyme B12-containing enzymes (50,51). The radical mechanism of action of these enzymes, involving coenzyme B 12 as essential cofactor, was initially proposed by Abeles and coworkers (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…All of the glycerol and diol dehydratases characterized so far belong to class II of coenzyme B12-containing enzymes (50,51). The radical mechanism of action of these enzymes, involving coenzyme B 12 as essential cofactor, was initially proposed by Abeles and coworkers (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes have a broad but uneven distribution among living forms and are vital to human health, are essential to the carbon cycle, and have important industrial applications (5, 27, 30). Historically, bacteria have provided excellent model systems for the study of vitamins, and recent investigations with several bacterial systems have found the molecular biology of B 12 -dependent processes to be unexpectedly complex (9,27,29,34,35). One of the most surprising findings in this area has been the identification of a polyhedral organelle involved in coenzyme B 12 -dependent 1,2-propanediol (1,2-PD) degradation by Salmonella enterica (9).…”
mentioning
confidence: 99%
“…Other B 12 -dependent enzymes (glycerol and diol dehydratase) undergo suicide inactivation by the substrate during catalysis (6,26,27). The inactivation involves irreversible cleavage of the Co-C bond of AdoCbl, forming 5Ј-deoxyadenosine and an alkylcobalamin-like species (27).…”
mentioning
confidence: 99%